Characterization methods for comprehensive evaluations of shielding materials used in an MRI. Issue 4 (26th February 2018) - Gross‐Weege, Nicolas; Dey, Thomas; Gebhardt, Pierre; Schug, David; Weissler, Bjoern; Schulz, Volkmar
Abstract : Purpose: In order to integrate electronic devices into a magnetic resonance imaging (MRI) scanner, shielding of the electronics with respect to the radio frequency (RF) transmit and receive system of the MRI scanner is required. Furthermore, MRI uses time‐varying low‐frequency magnetic fields for spatial encoding, i.e., the gradient magnetic fields. Time‐varying magnetic fields induce eddy currents in all conductive elements. The eddy currents result in opposing magnetic fields, which can cause distortions of the magnetic resonance (MR) image. As shielding of lower frequencies is not feasible in this respect, an ideal shielding element should be transparent for gradient magnetic fields while providing a high RF shielding effectiveness. Furthermore, it should offer a low susceptibility to prevent distortion of the main magnetic field of the MRI. In this work, we characterize the aforesaid shielding parameters of different shielding samples. Methods: We developed a nuclear magnetic resonance (NMR) probe to measure the magnetic fields to quantify the field distortions time‐resolvedly. The relative distortion was introduced as a proportionality constant relating the eddy‐current‐inducing field changes and the field distortions. The relative distortion was measured in the frequency range from 0 to 10 kHz for all shielding samples using the NMR probe. We characterized the shielding effectiveness of the samples in the frequency range from 1 to 150 MHz using a network analyzer. We conducted all measurements with three different materials, two carbon fiber composites and copper, each in various thicknesses. Results: The relative distortion of the magnetic fields induced by the carbon fiber composites samples was at least a factor of seven lower than the copper sample. A linear dependency on the sample thickness was measured for the main field distortion, the relative distortion and the shielding effectiveness. The relative distortion was roughly independent of the gradient frequency contrary to the shielding effectiveness, highly depending on the RF frequency. Conclusions: We presented a very sensitive method to characterize the distortion of the main field distortion and the gradient transparency using an NMR probe. We analyzed different shielding materials regarding the main field distortion, the gradient transparency, and the shielding effectiveness. From the tested materials, we identified a carbon fiber composite with the lowest distortion on the MRI.